2021
DOI: 10.1111/ppl.13373
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic stress‐induced anthocyanins in plants: Their role in tolerance to abiotic stresses

Abstract: Abiotic stresses, such as heat, drought, salinity, low temperature, and heavy metals, inhibit plant growth and reduce crop productivity. Abiotic stresses are becoming increasingly extreme worldwide due to the ongoing deterioration of the global climate and the increase in agrochemical utilization and industrialization. Plants grown in fields are affected by one or more abiotic stresses. The consequent stress response of plants induces reactive oxygen species (ROS), which are then used as signaling molecules to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
110
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 252 publications
(155 citation statements)
references
References 155 publications
2
110
1
1
Order By: Relevance
“… Maxton et al (2018) and Saikia et al (2018) observed higher antioxidant and proline activities in pepper and pulse plants inoculated with acdS -containing PGPB relative to those in non-inoculated plants under abiotic stress. The involvement of antioxidant and proline activities in the abiotic stress (cold and salt)-induced ROS scavenging and stress tolerance mechanism has been well demonstrated ( Mittler et al, 2004 ; Zhang et al, 2006 ; Xu et al, 2010 ; Mohammadian et al, 2012 ; Jaemsaeng et al, 2018 ; Naing et al, 2018 ; Kyu et al, 2019 ; Gupta and Pandey, 2020 ; Naing and Kim, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… Maxton et al (2018) and Saikia et al (2018) observed higher antioxidant and proline activities in pepper and pulse plants inoculated with acdS -containing PGPB relative to those in non-inoculated plants under abiotic stress. The involvement of antioxidant and proline activities in the abiotic stress (cold and salt)-induced ROS scavenging and stress tolerance mechanism has been well demonstrated ( Mittler et al, 2004 ; Zhang et al, 2006 ; Xu et al, 2010 ; Mohammadian et al, 2012 ; Jaemsaeng et al, 2018 ; Naing et al, 2018 ; Kyu et al, 2019 ; Gupta and Pandey, 2020 ; Naing and Kim, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different kinds of anthocyanins modified by methylation and hydroxylation at different positions of C6-C3-C6 carbon skeleton structures decide different colors varying from orange, red, and purple to blue in plants [7,19] (Table 1). The physiological role of anthocyanin in plants consists of defending against viral, bacterial, and fungicidal activities, absorbing excess visible and UV light irradiance, attracting pollinators and seed dispersers, and scavenging excess ROS under abiotic stresses [6,11,20]. Anthocyanins are synthesized in the endoplasmic reticulum and transported to accumulate in the vacuoles of a wide range of cells and tissues in both the vegetative and reproductive organs of plants [20].…”
Section: Anthocyanins Accumulation In Plantsmentioning
confidence: 99%
“…Therefore, anthocyanins have protective effects during plant development through absorbing excess UV light, preventing lipid peroxidation and suppressing the activity of ROS. Then, plants have evolved to the biosynthetic pathways of anthocyanins to resist various abiotic stresses including UV irradiation, drought, high salinity, and low temperature [11].…”
Section: Introductionmentioning
confidence: 99%
“…Color, particularly in flowers and fruits, contributes to desirability to customers. Presence of anthocyanins in fruits and vegetables may enhance pharmaceutical properties for human health and protect plants from oxidative stresses [1,2]. Anthocyanin synthesis is regulated by environmental factors and hormones [2].…”
Section: Introductionmentioning
confidence: 99%
“…Presence of anthocyanins in fruits and vegetables may enhance pharmaceutical properties for human health and protect plants from oxidative stresses [1,2]. Anthocyanin synthesis is regulated by environmental factors and hormones [2]. Sugars have been shown to stimulate the growth and storage of sink tissues and have endocrine activity in the regulation of photosynthesis, nutrient mobilization, and allocation [3,4].…”
Section: Introductionmentioning
confidence: 99%